Wage structure and public sector employment: Sweden versus the United States 1970 - 2002 - David Domeij; Lars Ljungqvist (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
Swedish census data and tax records reveal an astonishing wage compression; the Swedish skill premium fell by more than 30 percent between 1970 and 1990 while the U.S. skill premium, after an initial decline in the 1970s, rose by 8 - 10 percent. Since then both skill premia have increased by around 10 percentage points in 2002. Theories that equalize wages with marginal products can rationalize these disparate outcomes when we replace commonly used measures of total labor supplies by private sector employment. Our analysis suggests that the dramatic decline of the skill premium in Sweden is the result of an expanding public sector that today comprises roughly one third of the labor force, and that expansion has largely taken the form of drawing low-skilled workers into local government jobs that service the welfare state.
Keywords: E24; J31; 330; skill premium; employment; private sector; public sector; Sweden; United States; Lohnstruktur; Qualifikation; Öffentlicher Sektor; Privatwirtschaft; Vergleich; Schweden; USA